2006
DOI: 10.1523/jneurosci.4212-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Pentraxins Mediate Synaptic Refinement in the Developing Visual System

Abstract: Neuronal pentraxins (NPs) define a family of proteins that are homologous to C-reactive and acutephase proteins in the immune system and have been hypothesized to be involved in activity-dependent synaptic plasticity. To investigate the role of NPs in vivo, we generated mice that lack one, two, or all three NPs. NP1/2 knock-out mice exhibited defects in the segregation of eye-specific retinal ganglion cell (RGC) projections to the dorsal lateral geniculate nucleus, a process that involves activity-dependent sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
193
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(199 citation statements)
references
References 51 publications
(96 reference statements)
4
193
1
1
Order By: Relevance
“…Although Narp has been implicated in clustering AMPA receptors, its role in mediating synaptic plasticity remains to be fully clarified. As these mice performed normally in several classical assays of learning and memory reported here, it is not surprising that conventional measures of hippocampal long term potentiation are intact in Narp KO mice and in mice lacking Narp as well as the two other neuronal pentraxins, NP1 and NPR (Bjartmar et al, 2006). However, our detection of selective deficits suggest that Narp plays an important role in other types of synaptic plasticity critical for adjusting behavioral responses in the face of devaluation.…”
Section: Discussionmentioning
confidence: 56%
“…Although Narp has been implicated in clustering AMPA receptors, its role in mediating synaptic plasticity remains to be fully clarified. As these mice performed normally in several classical assays of learning and memory reported here, it is not surprising that conventional measures of hippocampal long term potentiation are intact in Narp KO mice and in mice lacking Narp as well as the two other neuronal pentraxins, NP1 and NPR (Bjartmar et al, 2006). However, our detection of selective deficits suggest that Narp plays an important role in other types of synaptic plasticity critical for adjusting behavioral responses in the face of devaluation.…”
Section: Discussionmentioning
confidence: 56%
“…The finding that silencing the expression of NP1 prevents the decrease in synaptophysin levels evoked by A␤ suggests that NP1 contributes to the synaptic damage evoked by A␤ and provides a molecular basis for this A␤-induced depression of synaptic transmission. The interpretation that NP1 regulates synaptogenesis and synaptophysin levels in response to changes in neuronal activity is supported by recent studies showing that NP1 knock-out mice exhibit defects in the segregation of eye-specific retinal ganglion cell projections to the dorsal lateral geniculate nucleus, a process that involves activity-dependent synapse formation (Bjartmar et al, 2006). Moreover, NP1 has been proposed to regulate synaptogenesis by forming pentraxin heterocomplexes with NP2 (Xu et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Nptx2 and other neuronal pentraxins are proposed to regulate activity-dependent synaptic plasticity via AMPA receptor clustering in hippocampal spines based primarily on in vitro studies; these functions suggest that neuronal pentraxins participate in learning and memory (O'Brien et al, 1999). However, deleting all three members of this family in mice resulted in a mild impairment of retinal activity, whereas hippocampal long-term potentiation and long-term depression appeared normal (Bjartmar et al, 2006). In the hypothalamus, others have suggested that lateral hypothalamic neuropeptides, hypocretin and MCH, use neuronal pentraxins to influence synapse formation of target neurons (Reti et al, 2002).…”
Section: Discussionmentioning
confidence: 99%